Identifying Actual Users in a Web Surfing Session using Tracing and Tracking - Umar Danjuma Maiwada; Aminu Aminu Muazu; Izaddeen Kabir Yakasai; Rufai Yusuf Zakari (JINAV: Journal of Information and Visualization, 2020)
The World Wide Web (www) has become an interactive medium for millions of Internet users across the world, daily visiting occur for various purposes. However, their behavior could be monitored by various service providers or company’s website they visited for several purposes. Thus, we can see that if certain data pre-processing techniques are practiced correctly, results will be of high quality and in turn provide substantial evidence of the user and its web session. This paper provides a way of knowing user behavior on the web. It explains the use of cookies: Cookies allow you to do many things such as log on to Internet Banking, have us 'remember' your log-in preferences, when logging on, a pop-up window appears stating the service is not available and to try later. A misspelled domain name in the address line. Lotteries that charge a fee to collect your winnings, apply for products and services online, and use financial tools like our ‘find and compare’ mortgage calculators., servers, and proxy logs with some scripting to be able not only to get a user’s IP address but also get personal information like age, identity, and any other credential as long as the user puts them down while using the web.